Exposure to Client-Perpetrated Violence in the Child Welfare Service: Prevalence and Outcomes Using Two Different Measurement Methods - Parveen, Sana (Journal of interpersonal violence, 2023)
This study compared how two different measurement methods of client-perpetrated violence influence findings on prevalence rates and mental health outcomes in a probability sample of 660 Norwegian public sector child welfare workers. Using a single-item self-labeling approach, 15.4% reported exposure to physical violence, and 19.3% reported exposure to threats. Using a 15-item behavioral experience inventory, the prevalence rates ranged from 4.4% to 65.7%. A comparison of these methods uncovered a high number of false negatives when using the single-item approach as 62.2% of those who indicated that they had not experienced any workplace violence when answering the single-item questions reported being exposed 1 to 2 times when responding to the behavioral inventory. Results based on the behavioral inventory further revealed that the most frequently occurring actions in the child welfare service were direct and indirect forms of threats (24.5%–65.7%), while the least reported behaviors were threats and violence including objects (4.4.%–9.1%). Although client-perpetrated violence was significantly associated with mental health problems (e.g., symptoms of anxiety, depression, and post-traumatic stress [PTS]) for both assessment methods, the magnitude of the effect sizes differed from η2 = .000 to η2 = .121. These findings highlight that the use of different measurement methods for workplace violence has significant consequences for the assessment of prevalence rates, as well as on results of associated outcomes. Consequently, the decision on how to assess workplace violence has practical implications for uncovering how prominent the issue is, as well as the way in which this negative workplace exposure is subsequently addressed and counteracted. Therefore, both scholars and the child welfare service, and similar fields in which workplace violence frequently occurs, should take these findings into consideration for future assessments.